Gait analysis in clinically healthy sheep from three different age groups using a pressure-sensitive walkway - Agostinho, Felipe S. [UNESP]; Rahal, Sheila Canevese [UNESP]; Araujo, Fabio A. P. [UNESP]; Conceicao, Renato T. [UNESP]; Hussni, Carlos Alberto [UNESP]; El-Warrak, Alexander O.; Monteiro, Frederico O. B. (Biomed Central Ltd., 2012)
Background: Understanding normal gait requires allowing for variations in normal patterns by the sex, age, and species in question. Therefore, the aim of this study was to evaluate kinetic and temporospatial parameters in clinically healthy sheep from three different age groups with a pressure-sensing walkway. The sheep were judged to be healthy based on the results of complete physical and orthopaedic examinations and had no history of lameness. Twenty-one clinically healthy female Santa Ines sheep were divided into three groups: G1 - seven animals, aged from 8 to 12 months and weighing 19.5-33 kg; G2 - seven individuals, aged from 2 to 4 years and weighing 26.5-42 kg; and G3 - seven sheep, aged more than 5 years and weighing 37.3-45 kg. The animals were examined from two directions: first on the left side and then on the right side of the handler. The data from the first five valid trials in each direction were collected for each sheep and analysed using the designated software. A trial was considered valid if the sheep walked within the correct velocity (1.1-1.3 m/s) and acceleration (from -0.15 to 0.15 m/s(2)) ranges. The peak vertical force (PVF), vertical impulse (VI), gait cycle time, stance time, swing time, stride length, and the percentage body weight distribution among the four limbs were determined.Results: No significant differences were observed, in either the forelimbs or the hind limbs, between the left and right sides or between the two directions for any of the variables. No significant temporospatial differences were found among the groups. Significant PVF (%BW) differences were observed in the forelimbs (G1 > G3) and hind limbs (G1 > G3), and significant VI differences were observed in the forelimbs (G1 > G3).Conclusions: Young healthy sheep differ from older sheep in the vertical forces they create when walking at the same velocity on a pressure-sensing walkway.